Treatment of Snoring with a Nasopharyngeal Airway Tube - Macario Camacho; Edward T. Chang; Camilo Fernandez-Salvador; Robson Capasso (Case Reports in Medicine)
Objective. To study the feasibility of a standard nasopharyngeal airway tube (NPAT) as treatment for snoring. Methods. An obese 35-year-old man, who is a chronic, heroic snorer, used NPATs while (1) the patient’s bedpartner scored the snoring and (2) the patient recorded himself with the smartphone snoring app “Quit Snoring.” Baseline snoring was 8–10/10 (10 = snoring that could be heard through a closed door and interrupted the bedpartner’s sleep to the point where they would sometimes have to sleep separately) and 60–200 snores/hr. Several standard NPATs were tested, consisting of soft polyvinyl chloride material raging between 24- and 36-French (Fr) tubes. Results. The 24 Fr tube did not abate snoring. The 26 Fr tube was able to abate the snoring sound most of the night (smartphone app: 11.4 snores/hr, bedpartner VAS = 2/10). The 28 and 30 Fr tubes abated the snoring sound the entire time worn (smartphone app: 0 snores, bedpartner VAS 0/10) but could not be tolerated more than 2.5 hours. The tube of 36 Fr size could not be inserted, despite several attempts bilaterally. Conclusion. Appropriately sized nasopharyngeal airway tubes may abate the snoring sound; however, as in this patient, they may be too painful and intolerable for daily use.